Effect of Long-Period Stacking Ordered(LPSO)Phases on the Corrosion Behavior of Mg-Gd-Y-Zn-Zr Alloys - XIA Xiang-sheng, ZHANG Kui, MA Ming-long, LIU Lei, MA Yanlong (Cailiao Baohu)
It is meaningful to study the effect of long-period stacking ordered(LPSO)phases content on the corrosion behavior of Mg-Gd-Y-Zn-Zr alloys for designing novel high-strong anti-corrosive Mg alloys.In this work, the electrochemical and corrosion behaviors of Mg-Gd-Y-Zn-Zr alloy in 5% NaCl aqueous solution were analyzed by metallographic observation, SEM, EDS, electrochemical test and immersion experiment, further confirming the effect of LPSO content on the corrosion resistance.Results showed that the Zn element played a dominant role in the formation and distribution of the LPSO phase in the Mg-Gd-Y-Zn-Zr alloys, there was no LPSO phase formed in the alloy when no Zn element was added.The volume fraction of the LPSO phase increased and the morphology changed from lamellar to bulk with the increase of Zn concentration.Moreover, during the corrosion process, an uniform and continuous corrosion product layer was formed on the surface of the alloy substrate.when the addition of Zn increased, the thickness of the corrosion product layer decreased, and the corrosion morphology of the alloys changed from general corrosion to local corrosion.Besides, the LPSO phase acted as the cathode of corrosion micro-cell during local corrosion process, accelerating the corrosion and dissolution of the alloy substrate.